1999
DOI: 10.1038/sj.onc.1202448
|View full text |Cite
|
Sign up to set email alerts
|

MDM2 overexpression generates a skin phenotype in both wild type and p53 null mice

Abstract: The MDM2 proto-oncogene is overexpressed in human tumours and regulates the activities of the tumour suppressors p53 and pRB. We created mice that overexpress MDM2 under the control of the CMV promoter. These mice did not display an increased tumour incidence, but rather a speci®c skin phenotype, characterized by desquamation and hyperkeratosis. Transgenic MDM2 was found to be overexpressed in the epidermis, a tissue that normally expresses high levels of MDM2. The phenotype appeared during the ®rst week after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
36
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 83 publications
5
36
0
Order By: Relevance
“…However, in our experiments, MDM2 induction seems to be independent of p53, since it also occurred in immortalized HaCaT keratinocytes in suspension (see also Dazard et al, 1997) and these cells have no transcriptionally active p53 (Lehman et al, 1993;Datto et al, 1995). Furthermore, Alkhalaf et al (1999) have found that an MDM2 transgene a ects the keratinocyte cell cycle in the absence of p53. Therefore, MDM2 may be induced independently of p53 as keratinocytes lose interaction with the extracellular matrix, and may play an important role in normal epidermal homeostasis, other than just controlling p53 activity.…”
Section: A Switch From P53 To Mdm2 Accompanies Initiation Of Epidermasupporting
confidence: 42%
See 1 more Smart Citation
“…However, in our experiments, MDM2 induction seems to be independent of p53, since it also occurred in immortalized HaCaT keratinocytes in suspension (see also Dazard et al, 1997) and these cells have no transcriptionally active p53 (Lehman et al, 1993;Datto et al, 1995). Furthermore, Alkhalaf et al (1999) have found that an MDM2 transgene a ects the keratinocyte cell cycle in the absence of p53. Therefore, MDM2 may be induced independently of p53 as keratinocytes lose interaction with the extracellular matrix, and may play an important role in normal epidermal homeostasis, other than just controlling p53 activity.…”
Section: A Switch From P53 To Mdm2 Accompanies Initiation Of Epidermasupporting
confidence: 42%
“…Consistently, papillomas induced in mouse p53 null epidermis progress more frequently to carcinomas than in the wild type tissue (Kemp et al, 1993). In addition, MDM2 transgenic mice have a transient epidermal phenotype that is reminiscent of ichthiosys or psoriasis, hyperproliferative lesions with thickening of di erentiating layers (Alkhalaf et al, 1999). Finally, knock out mice for p63, a negative regulator of p53, have a striking epidermal phenotype, consisting of a layer of scattered di erentiating-like keratinocytes Mills et al, 1999).…”
Section: A Molecular Switch Controlling Keratinocyte Growth?mentioning
confidence: 92%
“…Although MDM2's main partner is p53, it also has p53-independent functions. In a p53-null background, MDM2-transgenic animals display abnormalities, such as polyploidy of mammary epithelial cells and skin hyper-proliferation (Alkhalaf et al, 1999;Lundgren et al, 1997). Moreover, some MDM2 transgenic mice are predisposed to spontaneous tumour formation (Jones et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…In transgenic animals and in the absence of p53, MDM2 overexpression in the mammary gland leads to uncontrolled entry into S phase and polyploidy (Lundgren et al, 1997) and overexpression in the skin results in hyper-proliferation and inhibition of dierentiation (Alkhalaf et al, 1998). In cell culture, MDM2 inhibits muscle cell dierentiation and Myo-D dependent transactivation (Fiddler et al, 1996).…”
Section: Introductionmentioning
confidence: 99%